Seed Aid: The Importance of Local Decision-making (University of Denver Undergraduate Research Journal, 2023)
This policy paper focuses on the disconnect between donor and recipient states regarding seed aid and the implications of seed aid on local agricultural sovereignty and sustainability; it proposes that a reevaluation of international seed aid policies is needed. International food security organizations and food aid donors should prioritize local seeds for seed aid purposes to support local biodiversity and food sovereignty, and the stability and sustainability of local agricultural systems in the long term. Making adequate and accurate assessments of situations is crucial, and sourcing locally is an integral aspect of supporting local seed systems. The fundamental problem with the seed distribution system today is the limited availability of local seeds. Responding to food crises with an influx of seeds from donor countries poses a serious risk of undermining the livelihood security of farmers by disrupting local seed systems, risking local biodiversity, and resulting in genetic erosion. Therefore, efforts to increase food security in crisis situations should focus on supporting local seed production in the region or country whenever possible rather than bringing seeds in from outside or abroad.